Diagnostic Imaging and Medical Management of Acute Left-Sided Colonic Diverticulitis : A Systematic Review - Balk, Ethan M; Adam, Gaelen P; Bhuma, Monika Reddy; Konnyu, Kristin J; Saldanha, Ian J; Beland, Michael D; Shah, Nishit (Annals of internal medicine, 2022)
Clinicians need to better understand the value of computed tomography (CT) imaging and nonsurgical treatment options to manage acute left-sided colonic diverticulitis. To evaluate CT imaging, outpatient treatment of uncomplicated diverticulitis, antibiotic treatment, and interventional radiology for patients with complicated diverticulitis. MEDLINE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, Embase, CINAHL, and ClinicalTrials.gov from 1 January 1990 through 16 November 2020. Existing systematic reviews of CT imaging accuracy, as well as randomized trials and adjusted nonrandomized comparative studies reporting clinical or patient-centered outcomes. 6 researchers extracted study data and risk of bias, which were verified by an independent researcher. The team assessed strength of evidence across studies. Based on moderate-strength evidence, CT imaging is highly accurate for diagnosing acute diverticulitis. For patients with uncomplicated acute diverticulitis, 6 studies provide low-strength evidence that initial outpatient and inpatient management have similar risks for recurrence or elective surgery, but they provide insufficient evidence regarding other outcomes. Also, for patients with uncomplicated acute diverticulitis, 5 studies comparing antibiotics versus no antibiotics provide low-strength evidence that does not support differences in risks for treatment failure, elective surgery, recurrence, posttreatment complications, and other outcomes. Evidence is insufficient to determine choice of antibiotic regimen (7 studies) or effect of percutaneous drainage (2 studies). The evidence base is mostly of low strength. Studies did not adequately assess heterogeneity of treatment effect. Computed tomography imaging is accurate for diagnosing acute diverticulitis. For patients with uncomplicated diverticulitis, no differences in outcomes were found between outpatient and inpatient care. Avoidance of antibiotics for uncomplicated acute diverticulitis may be safe for most patients. The evidence is too sparse for other evaluated questions. Agency for Healthcare Research and Quality and American College of Physicians. (PROSPERO: CRD42020151246).